PERAN PENDAPATAN DALAM MEMODERASI PENGARUH SIKAP PADA KESEDIAAN MEMBAYAR PRODUK RAMAH LINGKUNGAN - Gunawan Komang Yogi Indra; Suprapti Ni Wayan Sri (Faculty of Economics and Business Udayana University, 2015)
The aim of this study is to determine the effect of attitudes toward willingness to pay of Philips LED bulb, with level of consumer income as moderating variable. The study was conducted in Denpasar City with sample size of 90 LED bulbs user but have not used the Philips brand. Sample was determined by purposive sampling and data were collected by using questionnaires distributed directly. The data were processed with Moderate Regression Analysis (MRA). The results of this study indicate that attitudes is positively affect willingness to pay, but the level of income is negatively affect willingness to pay. Nevertheless, income level are significantly moderate the relationship between attitude and willingness to pay, and the resultsshow a positive coefficient, which means that the income level strengthen the influence of attitude toward willingness to pay of Philips LED bulb